إدارة خدمة العملاء ودورها في رفع فعالية المصارف دراسة ميدانية على فروع المصرف العقاري في محافظة اللاذقية (مجلة جامعة اللاذقية- سلسلة العلوم الاقتصادية والقانونية, 2019)
يتمثل الهدف من هذا البحث في  بيان المفهوم العام لإدارة خدمة العملاء، وشرح أهم محاوره, وتوضيح عناصره.  وفي سبيل توضيح ذلك تم تقديم دراسة ميدانية لواقع إدارة خدمة العملاء للمصرف العقاري في محافظة اللاذقية، وذلك للتعرف إلى ما يلي: -  مدى تفهم المصرف محل الدراسة لحاجات عملائه. -  تحديد خدمات العملاء التي يقدمها المصرف محل الدراسة. - التعرف إلى مستوى جودة خدمة العملاء في المصرف محل الدراسة. - مدى حرص المصرف محل الدراسة على تجاوز توقعات العملاء. - آلية المصرف محل الدراسة في معالجة شكاوى العملاء. - مدى درجة رضا العملاء عن التعامل مع المصرف محل الدراسة - مدى ولاء العملاء للمصرف محل الدراسة وقدم البحث في النهاية ملخصاً لأهم النتائج التي تم التوصل إليها، كما قدم بعض المقترحات والتوصيات التي من شأنها رفع فعالية الخدمات المصرفية في فروع المصرف العقاري بمحافظة اللاذقية، والارتقاء بها لتنافس على الصعيد المحلي وعلى الصعيد العالمي. The objective of this research is showing the general concept of customer service management, and explaining the most important interlocutor and clarifying its elements. To clarify this issue, a survey study was performed on the issue of Customer Service Management of Real Estate Bank in the province of Lattakia, in order to know the following: - Understanding the extent of the bank under consideration to the needs of its customers. - Determining the customer service provided by the bank under consideration. - To identify the level of customer service quality in the bank under consideration. - The extent of interest of the bank under study, on exceeding the expectations of customers. - Automatic bank under consideration in dealing with customer complaints. - The degree of customer satisfaction for dealing with the bank under study - The loyalty of customers of the bank under study The research presented at the end a summary of the most important results that have been reached, and submitted some proposals and recommendations that will increase the efficiency of Real Estate Bank, and upgrading them to compete locally and globally.